Adults with reading difficulties demonstrate selective impairments in the fine neural tuning for print - Zhuang, Tongjie; Li, Yaowen; Tan, Yufei; Wang, Jiuju; Yue, Xiuyue; Xue, Licheng; Zhao, Jing (Frontiers in Neuroscience, 2025)
IntroductionNeural tuning for print, reflected in differential responses of the N170 component of event-related potentials to orthographic forms and other visual stimuli, serves as the neural basis for efficient visual word reading. Impaired neural tuning for print is well established in dyslexic children. Although many adults also experience reading difficulties, relatively few studies have examined whether such impairments exist in adults, particularly those who read Chinese, which differs markedly in visual and linguistic characteristics from alphabetic scripts.MethodsTo fill this gap, we assessed 20 high-level and 16 low-level adult readers who were the two extremes of the best and poorest readers of a database, which consisted of 308 college students. Using ERP techniques, we investigated two levels of neural tuning for print: coarse tuning (i.e., real, pseudo, false characters vs. stroke combinations) and fine tuning (i.e., real vs. pseudo vs. false characters).ResultsResults indicated that high-level adult readers exhibited both coarse and fine tuning for print. In contrast, low-level adult readers displayed a stronger N170 response to real and pseudo characters than to stroke combinations, suggesting intact coarse tuning. However, they showed no reliable N170 differences between real, false, and pseudo characters, indicating impaired fine tuning.ConclusionThese findings suggest a selective impairment in fine tuning for print among Chinese adults with reading difficulties and support the notion of persistent impairment in fine neural tuning for print among poor readers throughout development.